2016
DOI: 10.3389/fpls.2016.01840
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation of Proteins in Watery and Gel Saliva of Aphids

Abstract: Gel and watery saliva are regarded as key players in aphid–pIant interactions. The salivary composition seems to be influenced by the variable environment encountered by the stylet tip. Milieu sensing has been postulated to provide information needed for proper stylet navigation and for the required switches between gel and watery saliva secretion during stylet progress. Both the chemical and physical factors involved in sensing of the stylet’s environment are discussed. To investigate the salivary proteome, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 273 publications
(416 reference statements)
1
90
0
1
Order By: Relevance
“…In a previous study, the presence of salivary DNase II has been reported in the white-backed planthopper (Huang et al, 2018a;Miao et al, 2018), brown planthopper Huang et al, 2018a), and SBPH (Huang et al, 2018a). Although the composition of the saliva has been reported in > 10 Aphididae species, no salivary DNase II was found in these phloem-feeding aphids (van Bel & Will, 2016), which deserved further investigation. DNase II is an endonuclease that acts on phosphodiester linkages of DNA (Evans & Aguilera, 2003).…”
Section: Researchmentioning
confidence: 89%
“…In a previous study, the presence of salivary DNase II has been reported in the white-backed planthopper (Huang et al, 2018a;Miao et al, 2018), brown planthopper Huang et al, 2018a), and SBPH (Huang et al, 2018a). Although the composition of the saliva has been reported in > 10 Aphididae species, no salivary DNase II was found in these phloem-feeding aphids (van Bel & Will, 2016), which deserved further investigation. DNase II is an endonuclease that acts on phosphodiester linkages of DNA (Evans & Aguilera, 2003).…”
Section: Researchmentioning
confidence: 89%
“…In a study by Will et al (2007), an unknown factor in aphid saliva was found to prevent sieve tube clogging; it is tempting to speculate that this or other factors might also participate in the inoculation of viruses. Saliva components are also assumed to modify PTI, ETI and other defense responses, but hardly any candidates are known (reviewed by Kaloshian & Walling, 2016;van Bel & Will, 2016) and their possible role in facilitating virus transmission is even less explored. On a promising note, there are ongoing efforts to analyze the roles of aphid saliva in plant defense mitigation (i.e., Jaouannet et al, 2014;Kettles & Kaloshian, 2016;Mugford et al, 2016;Rodriguez et al, 2017) and we are hopeful that specific gaps in knowledge might soon be filled.…”
Section: Plant Defense-related Pathways Involved In Virus Transmissionmentioning
confidence: 99%
“…Plants possess many complex mechanisms to suppress herbivory, such as the production of phenols, alkaloids and proteins, as well as the initiation of induced plant defensive pathways involving ethylene, salicylic and jasmonic acids, and other plant hormones (Goggin, 2007;Elzinga & Jander, 2013). Evidence is accumulating that insect saliva proteins may be integral in the recognition and initiation of plant responses (Hogenhout & Bos, 2011;van Bel & Will, 2016). The results of proteome analyses of salivary components are reported in several insect orders, including Lepidoptera (Afshar et al, 2013;Rivera-Vega et al, 2017) and Diptera (Valenzuela et al, 2003;Assumpção et al, Correspondence: Nabil Killiny, Department of Plant Pathology, Citrus Research and Education Center, University of Florida, 700 Experiment Station Road, Lake Alfred, Florida 33850, U.S.A.…”
Section: Introductionmentioning
confidence: 99%
“…For most phloem-feeding hemipteran insects, watery and gel saliva are considered to be critical during stylet penetration and ingestion (van Bel & Will, 2016). During stylet penetration into the host tissues, gel saliva is involved in the coagulation and formation of salivary sheath, which protects, stabilizes and lubricates the stylet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation